Lysyl Hydroxylase Inhibition by Minoxidil Blocks Collagen Deposition and Prevents Pulmonary Fibrosis via TGF-β₁/Smad3 Signaling Pathway - Shao, Songjun; Zhang, Xiangning; Duan, Lingdi; Fang, Haiyan; Rao, Shanshan; Liu, Weijia; Guo, Bing; Zhang, Xiangyan (Medical science monitor, 2018)
BACKGROUND Idiopathic pulmonary fibrosis (IPF) is a deadly disease characterized by excessive collagen in the extracellular matrix (ECM) of the lungs. Collagen is the primary protein component of the ECM. However, the exact mechanisms underlying the formation and deposition of collagen in the ECM under normal and pathological conditions remain unclear. Previous studies showed that lysyl hydroxylase (LH) plays a crucial role in the formation of collagen. Minoxidil is an FDA-approved anti-hypertensive agent that inhibits LH that reduces fibrosis. In this study, we investigated the functional roles of LHs (LH1, LH2, and LH3) in pulmonary fibrosis and the anti-fibrotic effects of minoxidil. MATERIAL AND METHODS Patient serum samples were examined for their expression of procollagen-lysine, 2-oxoglutarate 5-dioxygenases (PLOD) 1-3, the genes encoding LH 1-3. Mice with bleomycin (BLM 2.5 mg/kg)-induced pulmonary fibrosis were administered a minoxidil solution (30 mg/kg) by oral gavage. RESULTS The PLOD mRNA levels were significantly higher in the IPF patients than in the healthy control subjects. Minoxidil suppressed the BLM-induced pulmonary fibrosis in vivo. These effects were associated with blocking TGF-β₁/Smad3 signal transduction and attenuating the expression and activity of LHs, resulting in decreased collagen formation, thus reducing the pulmonary fibrosis. The anti-fibrotic effects of minoxidil may be mediated through competitive inhibition of LHs activity, resulting in decreased pyridine cross-link formation and collagen production and deposition. CONCLUSIONS The results of this study suggest that LH represents a target to prevent or treat pulmonary fibrosis, and minoxidil may provide an effective agent to inhibit LHs.